Efficient and stable electro-Fenton treatment of antibiotics-containing wastewater over NiFe bimetal atom catalyst via flow-through micro-nanoscale spatial confinement system - Zhang, Danyu; Chen, Yarong; Wang, Yuchen; Zhang, Hao; Tang, Haifang; Sun, Xuhui; Liu, Qingquan; Liu, Chengbin (Journal of hazardous materials, 2025)
The engineering application of electro-Fenton process is subject to limited availability of •OH caused by mass transfer limitation and the short lifetime of •OH in water. In this study, an efficient electro-Fenton treatment process is developed by constructing a flow-through micro-nanoscale spatial confinement electrode with NiFe bimetal atom catalyst for oxygen reduction reaction (ORR). The NiN4-FeN4 active sites are anchored onto carbon nanotubes grown in the tunnel of carbonized pine wood (NiFe-NCNTs-CP). Efficient generation of •OH is achieved through 3-electron ORR over NiFe-NCNTs-CP. Because of the unique flow-through micron-nanoscale confinement environment, the concentration of accumulated •OH reaches as high as 6092 μmol L−1 min−1 even though the water flux is up to 236 L m−2 h−1 (equivalent to a retention time of 60 s). The proposed electro-Fenton system achieves 100 % removal of florfenicol, thiamphenicol, chloramphenicol, sulfamethoxazole, and tetracycline in water within just 60 s (C0=20 mg L−1, pH=7, 0.7 V vs SCE). The proposed continuous flow process maintains highly stable for treating actual medical wastewater within 8 days, achieving discharge standards and eliminating the antibacterial activity of medical wastewater. Furthermore, the proposed process showed a low energy consumption of only 7.35 kWh kg (COD)−1. This study presents a highly practical electro-Fenton process for organic wastewater treatment. [Display omitted] •Flow-through micron-nanoscale spatial confinement electro-Fenton system is constructed.•High-efficiency production of •OH via ORR is realized.•The mechanism of •OH production over NiN4-FeN4 active sites is revealed.•100 % antibiotic removal efficiency is achieved within 60 s.•The system stably treats real medical wastewater, meeting discharge standards and eliminating its antibacterial activity.